On the performance of signal detection algorithms in flat-fading and frequency-selective MIMO channels - Jorswieck, E.; Jungnickel, V.; Haustein, T.; Pohl, V.; von Helmolt, C. (2002 IEEE 55th Vehicular Technology Conference, 2002)
In this work, we study a single-user MIMO transmission link in flat and frequency selective Rayleigh fading. The impact of the time dispersion in the channel on the performance of the signal separation algorithms is analyzed. We discuss the mismatch case in which the receiver assumes a flat-fading channel but is confronted actually with a frequency-selective MIMO channel. We give an analytical formula for the uncoded bit error rate in the mismatch case for zero-forcing detection. It is shown how to generalize the well known signal detection algorithms for flat-fading MIMO channels to the frequency-selective case. In particular, the performance and complexity of these algorithms is compared. A suboptimal algorithm with reduced complexity is proposed and compared to the optimal algorithms. All theoretical results are confirmed by numerical simulations.